Contributions to a Literature Review about the Theory and Praxis of Educational Curriculum - Majad Rondón, Musa Ammar (2015)
The purpose of this article is to make an approximation to a literature review of the conceptualization of the theory and praxis of the educational curriculum, either as a model or as a curricular profile because multiple lines of thought on this matter have been fostered. All this has led to the development of various theories which, taken together, are a reflection of the different existing conceptions when addressing the elements of education. In this regard, a literature review and interpretation of texts under the critical - reflective paradigm was made. It is established that from the emancipatory-theoretical approach of the curriculum and the curriculum approach based on a reflection on the practice, a kind of harmony can be deduced, in which both have as a binding element a dialectic between theory and practice.